Evaluasi dan Perbaikan Desain Antarmuka Pengguna Dengan Menggunakan Metode Human-Centered Design (HCD), WEBUSE, WCAG 2.0, Research-Based Web Design & Usability Guidelines, dan Importance - Performance Analysis (IPA) (Studi Kasus: PT Showa Indonesia Mfg.) - Rasyid Asis Perdana; Komang Candra Brata; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
This research has a purpose to evaluate and improvement the website user interface design of PT Showa Indonesia Mfg. by adoption the Human Centered Design approach of ISO 9241-210, a standard that provides guidance for interactive system development stages involving humans as users in every system development process, in this case involving stakeholders and users. To find out the context and needs of users using the Website Usability Evaluation (WEBUSE) questionnaire and on design using general design guidance comes from Research-Based Web Design & Usability Guidelines and Web Content Accessibility Guidelines (WCAG) 2.0. The results of the website interface improvement design were evaluated and the results were compared with the results of the original design evaluation, this evaluation using Importance-Performance Analysis (IPA). This analysis aims to determine whether there is an increase after the design improvement process is done. The results of IPA evaluation of PT SIM website are nine'th attributes of problems and entered in quadrant â€œpriorities for improvementsâ€. While in the design improvement of conformity and aspects of the gap (GAP) states that there has been an increase. Then the nine'th attributes of the problem has increased the entry into the quadrant â€œkeep up the good workâ€.